Optimal Design of Hydrogen Based Wind-Microhydro Using Genetic Algorithm - Soedibyo Soedibyo; Heri Suryoatmojo; Imam Robandi; Mochamad Ashari (Institute of Advanced Engineering and Science, 2012)
The target of stand-alone hybrid power generation system was to supply the load demand with high reliability and economically as possible. To design these criteria the optimal design of the proposed configuration should be done by using intelligent optimization technique. This study utilized Genetic Algorithm method to determine the optimal capacities of hydrogen, wind turbines and micro hydro unit according to the minimum cost objective functions that relate to these two factors. In this study, the cost objective function included the annual capital cost, annual operation maintenance cost, annual replacement cost and annual customer damage cost. The proposed method had been tested in the hybrid power generation system located in Leuwijawa village in Central Java of Indonesia. Simulation results showed that the optimum configuration can be achieved using 19.85 ton of hydrogen tanks, 21 x 100 kW wind turbines and 610 kW of micro hydro unit respectively. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1326